2004
DOI: 10.1111/j.1467-6494.2004.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience and Positive Emotional Granularity: Examining the Benefits of Positive Emotions on Coping and Health

Abstract: For centuries, folk theory has promoted the idea that positive emotions are good for your health. Accumulating empirical evidence is providing support for this anecdotal wisdom. We use the broaden-and-build theory of positive emotions (Fredrickson, 1998; as a framework to demonstrate that positive emotions contribute to psychological and physical well-being via more effective coping. We argue that the health benefits advanced by positive emotions may be instantiated in certain traits that are characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
870
1
48

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,255 publications
(1,021 citation statements)
references
References 108 publications
51
870
1
48
Order By: Relevance
“…Decreases in symptomatology could suggest a direct impact of resilience, that having gone through the initial job loss enhances the ability to respond to later occurrences, thus providing a form of "immunity" to subsequent exposures (Carver 1998). Alternatively, the resilience may operate through the style in which individuals cope with the stress of unemployment (Lazarus and Folkman 1984;Grossi 1999;Tugade et al 2004), or via related behavior, notably post-displacement job seeking and labor market activity (Leana and Feldman 1995;Kanfer et al 2001;McKee-Ryan et al 2005). Reasons other than resilience are, of course, also possible.…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in symptomatology could suggest a direct impact of resilience, that having gone through the initial job loss enhances the ability to respond to later occurrences, thus providing a form of "immunity" to subsequent exposures (Carver 1998). Alternatively, the resilience may operate through the style in which individuals cope with the stress of unemployment (Lazarus and Folkman 1984;Grossi 1999;Tugade et al 2004), or via related behavior, notably post-displacement job seeking and labor market activity (Leana and Feldman 1995;Kanfer et al 2001;McKee-Ryan et al 2005). Reasons other than resilience are, of course, also possible.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, others have reported that positive affect is associated with greater social support, optimism, and adaptive coping responses, whereas negative affect is associated with negative relationships, pessimism, and avoidant coping . Other research suggests that positive affect may produce patterns of thought and behavior that are flexible, creative, and open to new information, and might therefore promote adaptive coping by increasing one's personal resources (Tugade, Fredrickson, & Feldman Barrett, 2004). Fourth, it may be possible that having a physical disorder leads to decreased levels of positive affect or increased levels of negative affect, owing mainly either to the pain, discomfort, or physical limitations concomitant to such disorders.…”
Section: Discussionmentioning
confidence: 99%
“…La resiliencia disminuye el grado de infarto de miocardio, al afectar la respuesta inflamatoria, que muestra un efecto protector (Arrebola-Moreno et al, 2014), y se correlaciona negativamente con la duración de las reactividad cardiovascular, devolviendo rápidamente a los niveles basales de fisiológicos de respuesta después de una activación emocional negativa (Tugade, Fredrickson, & Feldman Barrett, 2004). Además, los pacientes con enfermedad coronaria con alta resiliencia logran niveles de colesterol más bajos y un mejor rendimiento físico (Chan, Lai, & Wong, 2006).…”
Section: Resiliencia Y Salud Físicaunclassified